Household attitudes and institutional positions towards shared vehicles and autonomous automobility. - Kovacs, Ferenc Stephen (Curtin University, 2025)
This thesis examined household and planning attitudes to shared vehicles and autonomous automobility. Many residents had used ridesourcing and held favourable attitudes to shared autonomous vehicles to reduce car ownership costs. Planners had enabled shared vehicles and many were facilitating autonomous automobility. However, contextual and institutional differences suggest autonomous vehicles will have variable spatial impacts, including the extent to which ridesharing and its integration with transit can mitigate traffic growth from road transport automation.